2005
DOI: 10.1016/j.micres.2004.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Alginate acetylation influences initial surface colonization by mucoid Pseudomonas aeruginosa

Abstract: Mucoid strains of Pseudomonas aeruginosa overproduce the exopolysaccharide alginate, which is substituted with O-acetyl groups. Under non-growing conditions in phosphate buffer, a mucoid clinical strain formed microcolonies on steel surfaces, while an acetylation-defective mutant was unable to form cell clusters. Enzymatic degradation of alginate by alginate lyase prevented microcolony formation of the mucoid parent strain. In a continuous-culture flow-cell system, using gluconate minimal medium, the mucoid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 38 publications
7
65
0
1
Order By: Relevance
“…A mutation in algJ synthesizes alginate lacking O-acetyl groups, and this strain is significantly impaired in surface attachment and biofilm development (48). A separate study demonstrated that alginate acetylation was necessary for the aggregation of bacteria into microcolonies (68). Thus, it appears that acetyl groups help mediate interactions between neighboring cells and surface colonization, and these factors are important in the ability of strains to form robust biofilms.…”
Section: Figmentioning
confidence: 99%
“…A mutation in algJ synthesizes alginate lacking O-acetyl groups, and this strain is significantly impaired in surface attachment and biofilm development (48). A separate study demonstrated that alginate acetylation was necessary for the aggregation of bacteria into microcolonies (68). Thus, it appears that acetyl groups help mediate interactions between neighboring cells and surface colonization, and these factors are important in the ability of strains to form robust biofilms.…”
Section: Figmentioning
confidence: 99%
“…Results from several independent laboratories have shown that overproduction of acetylated alginate leads to significant architectural and morphological changes in the biofilm [10][11][12][13]. This translates into increased resistance to antimicrobials [10] or IFN-gamma-mediated killing by cells of the innate immune system [14].…”
Section: Alginatementioning
confidence: 99%
“…In many bacteria, O-acetylation alters the physicochemical properties of capsule by changing the conformation of capsular repeat units (13) or increasing viscosity (14). O-acetylation also alters the host-pathogen interaction by creating immunogenic epitopes (11,13,15), by neutralizing reactive chlorine species (16,17), and/or by mediating resistance to lysozyme and complement deposition (18)(19)(20)(21).…”
mentioning
confidence: 99%